2017
DOI: 10.5539/jms.v7n4p150
|View full text |Cite
|
Sign up to set email alerts
|

Job Stress in Journalism: Interaction between Organisational Support and Job Demands–Resources Model

Abstract: This study aims to analyse the impact of job demands and job resources on job stress among journalists in Jordan. In addition, the moderation effect of organisational support on such relationship is assessed in this research. A questionnaire survey was conducted among journalists working in daily newspapers in Jordan. This study used multiple and hierarchical regression analyses and determined a significant and positive relationship amongst emotional demands, job insecurity, and task significance on job stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…(2018) mengatakan, job stress merupakan respons tubuh terhadap tuntutan dan keadaan yang dihadapi para karyawan. Menurut Muala (2017), job stress adalah respons bahaya yang ditunjukkan fisik dan emosional yang terjadi ketika syarat-syarat dalam pekerjaan tidak sesuai dengan kemampuan, sumber daya, atau kebutuhan pekerja. Jehangir et.…”
Section: Kajian Literaturunclassified
“…(2018) mengatakan, job stress merupakan respons tubuh terhadap tuntutan dan keadaan yang dihadapi para karyawan. Menurut Muala (2017), job stress adalah respons bahaya yang ditunjukkan fisik dan emosional yang terjadi ketika syarat-syarat dalam pekerjaan tidak sesuai dengan kemampuan, sumber daya, atau kebutuhan pekerja. Jehangir et.…”
Section: Kajian Literaturunclassified
“…Pierce et al (2009)'s study reported that job demands, along with time pressure, can cause job-related negative emotions and mental pressures. Muala (2017) applied the JD-R model in a news agency setting, which showed that high job demands, and low job resources could cause job stress (i.e., one type of negative job engagement outcome) among journalists in the news organisations Up-to-date, scholars are also highly interested in modifying and extending the JD-R model by inviting other relevant factors to become more suitable for the specific research context. For instance, Xanthopoulou et al (2009) considered personal resources into the JD-R model, such as optimism, self-efficacy and organisational-based self-esteem, which would collaborate with job resources to predict the outcomes of job engagement.…”
Section: Jd-r Modelmentioning
confidence: 99%
“…Arthur, 1994; Benkhoff, 1997) are even categorical that inability to meet employees’ need negatively affects their commitment to duty. Muala (2017) studied journalists in Jordan to ascertain, among others, job insecurity, job demands and stress of journalists and found that job demands play an essential role in job stress. Such job demands may also include coverage of protest under a very volatile circumstance.…”
Section: Theoretical Frameworkmentioning
confidence: 99%